Consistency of VDJ Rearrangement and Substitution Parameters Enables Accurate B Cell Receptor Sequence Annotation - Ralph, Duncan K.; Matsen, Frederick A., IV (PLOS Computational Biology, 2016)
Author Summary The binding properties of antibodies are determined by the sequences of their corresponding B cell receptors (BCRs). These BCR sequences are created in “draft” form by VDJ recombination, which randomly selects and deletes from the ends of V, D, and J genes, then joins them together with additional random nucleotides. If they pass initial screening and bind an antigen, these sequences then undergo an evolutionary process of mutation and selection, “revising” the BCR to improve binding to its cognate antigen. It has recently become possible to determine the BCR sequences resulting from this process in high throughput. Although these sequences implicitly contain a wealth of information about both antigen exposure and the process by which humans learn to resist pathogens, this information can only be extracted using computer algorithms. In this paper, we employ a computational and statistical approach to learn about the VDJ recombination process. Using a large data set, we find consistent and detailed patterns in the parameters, such as amount of V gene exonuclease removal, for this process. We can then use this parameter-rich model to perform more accurate per-sequence attribution of each nucleotide to either a V, D, or J gene, or an N-addition (a.k.a. non-templated insertion).